Activation of defence responses on cocoa against Verticillium wilt by natural extracts and acibenzolar-S-methyl - Pereira, Ricardo Borges; Resende, Mário Lúcio Vilela de; Júnior, Pedro Martins Ribeiro; Amaral, Daniel Rufino; Lucas, Gilvaine Ciavareli; Cavalcanti, Fábio Rossi (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to assess the potential of fungal and plant extracts on the reduction of Verticillium wilt of cocoa, the activities of the enzymes peroxidase and polyphenoloxidase, as well as the lignin content. Seedlings of cocoa were sprayed with the mycelial filtrate of Rhizopus sp. (FMR), chitosan from Rhizopus sp. (QMR) and Trichoderma sp. (QMT), extracts of fresh and dry passion fruit peel, methanolic extract from dry passion fruit peel (MMS) and acibenzolar-S-methyl (ASM – 0.2 mg mL-1) and, inoculed with Verticillium dahliae, seven days later. ASM reduced the cocoa Verticillium wilt in 38.0%. The extract FMR, QMT, MMS and QMR presented as well reductions of 22.8, 20.1, 19.2 and 15.7%, respectively, in comparison with the control. Plants sprayed with ASM or FMR followed by inoculation presented increase of peroxidase activity at the 8th day after spraying, compared to the respective controls, with peak at the 18th day after spraying. ASM and FMR increased polyphenoloxidase activity at the 4th day after spraying. Higher lignin concentrations were obtained in plants treated with FMR and FMR following by inoculation. FMR may constitute a potential resistance inducer for the management of the Verticillium wilt of cocoa.